2001
DOI: 10.1136/gut.48.4.548
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis of hepatic stellate cells: involvement in resolution of biliary fibrosis and regulation by soluble growth factors

Abstract: Background-Activated hepatic stellate cells (HSC) are central to the pathogenesis of liver fibrosis, both as a source of fibrillar collagens that characterise fibrosis and matrix degrading metalloproteinases and their tissue inhibitors, the TIMPs. Aims-To test the hypothesis that HSC apoptosis is critical to recovery from biliary fibrosis and that soluble growth factors may regulate HSC survival and apoptosis. Methods-Rats (n=15) were subjected to bile duct ligation for 21 days, after which biliodigestive anas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
208
1
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(221 citation statements)
references
References 24 publications
7
208
1
5
Order By: Relevance
“…In addition, direct interactions with ECM components leading to activation of the FAK/PI-3K-dependent survival pathway [26], and the secretion of TIMP-1 thereby preventing MMP-dependent matrix degradation [27] may promote the survival of activated HSC. Finally, autocrine stimulation by cytokines like TGF-β or IGF-1 was regarded as a potential protective mechanism [28,29]. In the in vitro model presented here, co-incubation of HSC with CM of steatotic hepatocytes significantly reduced STS-induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, direct interactions with ECM components leading to activation of the FAK/PI-3K-dependent survival pathway [26], and the secretion of TIMP-1 thereby preventing MMP-dependent matrix degradation [27] may promote the survival of activated HSC. Finally, autocrine stimulation by cytokines like TGF-β or IGF-1 was regarded as a potential protective mechanism [28,29]. In the in vitro model presented here, co-incubation of HSC with CM of steatotic hepatocytes significantly reduced STS-induced apoptotic cell death.…”
Section: Discussionmentioning
confidence: 87%
“…6G). Furthermore, apoptosis in HSC-T6 cells was induced by serum deprivation plus CHX treatment (32). A significant increase in apoptosis was achieved in HSCs after 4-h incubation with CHX.…”
Section: Mir-21 Pdcd4 and Ap-1 Formed An Autoregulatory Feedback Lomentioning
confidence: 98%
“…9 Decreased activity of TIMPs' , apoptosis of HSCs, and even reversal of activated HSCs to a more quiescent state are suggested as key events for fibrosis resolution. 10,11 As activated HSCs are a major source of fibrillar collagens and of TIMPs, clearance of HSCs could facilitate matrix remodeling. Indeed, several studies have demonstrated that clearing HSCs reverses fibrosis.…”
mentioning
confidence: 99%